Factors Influence Entrepreneur’s Disability Independence in Bantul District - Anik Puji Handayani (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2021)
Micro small and medium enterprises (MSME) play an important role in Indonesia’s economic growth. Indonesia need to improve awareness and readiness as well as taking more optimal advantages for MSMEs by improving their competitiveness. One of the MSME’s entrepreneurs in Indonesia consist of psychical disabilities entrepreneurs. This research analyzes the factors that influence the independence of MSMEs disability in Bantul District. These factors consist of entrepreneur characteristics, business capital, and business revenue. The analytical method used is partial least square (PLS). The result shows the characteristic of disability entrepreneurs that do not affect the independence of MSME’s disabilities. Meanwhile, business capital significantly affect the independence of MSME’s disability. This research also found that business revenue significantly affects the independence of MSME’s disability.